(untitled) (Journal of Telenursing (JOTING), 2025)
This study analyzes the relationship between work fatigue and psychological stress in mining workers undergoing a long work roster system. This study uses a quantitative method with a descriptive and analytical approach. The results showed that the weakening of work activities was mainly in the mild fatigue category of 79 people (98.8%), while physical weakening and motivational weakening were all in the low fatigue category of 80 people (100%). Meanwhile, in terms of psychological stress, most respondents were in the moderate stress category, such as in the variables of role ambiguity (57.5%), role conflict (65%), quantitative overload (65%), qualitative overload (73.8%), career development (66.3%), and responsibility for others (60%). The results of the Pearson Correlation test showed a correlation coefficient value (r) of 0.510, which indicated a moderate positive relationship between work fatigue and psychological stress. The significance value (p) of 0.000 indicates that the relationship is statistically significant (p <0.05). This study concludes an essential relationship between work fatigue and psychological stress in mining workers with a long work roster system. Keywords: Work Fatigue, Work Roster, Psychological Stress